2021
DOI: 10.1186/s13102-021-00392-z
|View full text |Cite
|
Sign up to set email alerts
|

Muscle synergies for the control of single-limb stance with and without visual information in young individuals

Abstract: Purpose Single-limb stance is a demanding postural task featuring a high number of daily living and sporting activities. Thus, it is widely used for training and rehabilitation, as well as for balance assessment. Muscle activations around single joints have been previously described, however, it is not known which are the muscle synergies used to control posture and how they change between conditions of normal and lack of visual information. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In addition, these exercises can activate nerves to improve proprioception so that they are considered effective in improving balance and functional walking. Leg muscles are important in maintaining postural balance and joint stability in addition to core muscles [20,21]. This statement is supported by Kusnanto et al, in Malasari et al, who stated that balance training could increase muscle fibre (hypertrophy).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, these exercises can activate nerves to improve proprioception so that they are considered effective in improving balance and functional walking. Leg muscles are important in maintaining postural balance and joint stability in addition to core muscles [20,21]. This statement is supported by Kusnanto et al, in Malasari et al, who stated that balance training could increase muscle fibre (hypertrophy).…”
Section: Discussionmentioning
confidence: 89%
“…During the single-leg stance, the APs were primarily responsible for controlling the movement of the body’s center of mass in the anterior–posterior direction [ 17 , 40 , 41 ]. A previous study has shown that the first muscle synergy can primarily be attributed to an ankle control strategy, while the second muscle synergy is associated with a knee control strategy [ 16 ]. The result of this study found that three major muscle synergies were involved in the single-limb stance, two of which were ankle-dominant, and one was knee-dominant.…”
Section: Discussionmentioning
confidence: 99%
“…While both the AP strength and the KE strength are important for maintaining single-leg balance in older individuals, this study suggests that the AP strength may be more important. The biomechanical explanation for this finding is that the APs are more directly involved in controlling the movement of the body’s center of mass during the single-leg stance, whereas the KEs play a more supportive role in this process [ 16 ]. When the body experiences a balance perturbation, such as an unexpected push or slip, the ankle muscles are among the initial muscles to be activated in order to restore balance [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When vision is impaired, the sensory input of visually impaired individuals appears as the vestibular and proprioception compensative mechanism ( Schwesig et al, 2011 ). Labanca et al (2021) compared with eyes-opened, the ankle muscle group co-activation and ankle strategy of young people were more obvious when the posture was unstable, the neuromuscular system could improve the stability by regulating the activity of the ankle muscle group in the eyes-closed state. However, it is unclear whether myopia affects muscle activation.…”
Section: Introductionmentioning
confidence: 99%